Letter from Sam Grant Jr. to James Curtis Booth - Grant, Sam, Jr. (1863)
Sam Grant Jr. writes to James Curtis Booth (1810-1888) asking to procure a $5 or a $2.50 unstamped gold piece. Booth notes on the letter verso that the Director will allow it.
Keywords: Booth, James Curtis, 1810-1888; United States Mint; Mint of the United States